Properties of glutamate dehydrogenase in developing legume fruit. I. The effects of chelating agents - Mahmood, Marziah (1982)
A study was conducted to investigate the effects of EDTA. and Chelex-lOO on the glutamate dehydrogenase activity from a crude extract of the developing seeds of Lupinus angustifolius. The enzyme was not inhibited by Chelex-lOO; instead it was highly stimulated and its activity, when treated with Chelex-lOO, was higher than that of the control. Glutamate dehydrogenase, however, was inhibited by 5mM EDTA, stimulated at 30mM EDTA, and inhibited again at 45mM EDTA.